In Vitro Comparative Assessment of Composite Nanoleakage Using Various Dentine Surface Treatments - Mohammed H. Abbood; Raghad A. Al-Hashimi (College of Dentistry/ University of Baghdad, 2016)
Background: The treatment of dental tissues proceeding to adhesive procedures is a crucial step in the bonding protocol and decides the clinical success ofrestorations. This study was conducted in vitro, with the aim of evaluating thenanoleakage on the interface between the adhesive system and the dentine treated by five surface modalities using scanning electron microscopy and energydispersiveX-ray spectrometry. Materials and methods: Twenty five extracted premolars teeth were selected in the study. Standardized class V cavities were prepared on the buccal and lingual surfaces then the teeth divided into five main groups of (5 teeth in each group n=10) according to the type of dentine surface treatment that was used: Group (A): dentine was conditioning with Er, Cr: YSGG laser. Group (B): dentine was conditioning with (Er, Cr: YSGG laser + acid). Group (C): dentine was conditioning with (acid + Er, Cr: YSGG laser). Group (D): dentine was conditioning with acid etch. Group (E): dentine was conditioning with acid + 10% sodium hypochlorite. For All the teeth SBMP adhesive were used and restored with Z250 composite restoration then all specimens were subjected to thermocycling 500 cycles, at 5° to 55 °C. The teeth were soaked in silver nitrate suspension. Then the teeth sectioned bucco-lingually across the centre of the restorations. The specimens were characterized using scanning electron microscopy and the amount of nanoleakage was measured by EDX spectro-analysis to identify the existence of metallic silver particles. Results: Data were analysed statistically by one way ANOVA test and (LSD) Tests. The results showed that there were statistically highly significant differences among all groups of the present study.The resultshowed that the acid and laser (group III) exhibited the lowest mean value of nanoleakage at around (6.14 %), whereas the highest mean value of nanoleakage (12.83 %) was determined by the only acid (group IV). Conclusions: Treating the acid etched dentine with Er: Cr: YSGG laser showed promising results as it exhibits lowest amount of nanoleakage of the adhesive bonding system.